Greek Myth and Fantasy as Portrayed in â€œBlack Swanâ€ Movie Script by Andrez Heinz - Wanda Firanci; Muarifuddin; Nurisrafyan Sofian (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2022)
This study aimed to analyze racism in The Man Who Knew Infinity movie usingParadies, Harris, and Andersonâ€™s theory. The Man Who Knew Infinity thatreleased in 2016 is a film directed by Matthew Brown that features the characterof a genius mathematician from India named Srinivasa Ramanujan who wants topublish his formula about mathematics in Trinity College. As an Indian,Ramanujan experienced various acts of racism committed by the British, bothmentally and physically. This study used a descriptive qualitative method. Thedata collected through four steps, such as watching, screenshotting, note taking,and identifying the data. The result of this study showed that the main characterexperienced racism because of his race and nationality. The kinds of racism thatthe main character experienced namely stereotypes, prejudice, anddiscrimination.